2007
DOI: 10.1002/cncr.22812
|View full text |Cite
|
Sign up to set email alerts
|

An apoptotic molecular network identified by microarray: On the TRAIL to new insights in epithelial ovarian cancer

Abstract: Protein‐imprinted soft‐gel composite microspheres with magnetic susceptibility (MS‐PIGMs) were prepared by inverse suspension polymerization using Fe3O4 particles as magnetically susceptible component and bovine serum albumin and lysozyme (Lyz) as templates, respectively. The average content of magnetically susceptible component (Fe3O4) inside MS‐PIGMs was determined using thermogravimetric analyzer, and the magnetic characteristics of MS‐PIGMs were measured by vibrating sample magnetometer. The results showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 56 publications
2
24
0
Order By: Relevance
“…The contribution of c-FLIP L expression in identifying patients that do not yet display p53 nuclear accumulation supports a role for this molecule at the tumor onset, while p53 overexpression is apparently more related to later stages of the disease. Consistent with our finding, other authors (Horak et al 2005, Ouellet et al 2007, by studying deregulation of TRAIL cascade in EOC patients, identified c-FLIP L mainly expressed in early-stage ovarian cancer further suggesting that this survival factor is expressed by tumor cells when other mechanisms of apoptosis resistance, like loss of p53 function, are not yet present.…”
Section: Discussionsupporting
confidence: 92%
“…The contribution of c-FLIP L expression in identifying patients that do not yet display p53 nuclear accumulation supports a role for this molecule at the tumor onset, while p53 overexpression is apparently more related to later stages of the disease. Consistent with our finding, other authors (Horak et al 2005, Ouellet et al 2007, by studying deregulation of TRAIL cascade in EOC patients, identified c-FLIP L mainly expressed in early-stage ovarian cancer further suggesting that this survival factor is expressed by tumor cells when other mechanisms of apoptosis resistance, like loss of p53 function, are not yet present.…”
Section: Discussionsupporting
confidence: 92%
“…Drug-induced DR5 up-regulation is more frequently reported than DR4 up-regulation (22,27,31). Several other studies have reported the important role of DR5 in ovarian cancer (12,13). Moreover, in ovarian cancer specimens obtained before and after cisplatin treatment, DR5 expression increased from 37% to 74% after chemotherapy, whereas DR4 staining remained unaltered (32).…”
Section: Discussionmentioning
confidence: 80%
“…The role of DR5 has been implied in ovarian cancer, because hypermethylation of the DR4 promoter and reduced expression of DR4 frequently occur in ovarian cancers (12). Moreover, univariate analysis showed an association for high DR5 expression with decreased survival in ovarian cancers (13). In addition, use of rhTRAIL combined with cisplatin enhanced apoptosis and growth inhibition in several ovarian cancer cell lines, which was related to cisplatininduced DR4 and DR5 cell surface expression (14).…”
mentioning
confidence: 99%
“…Secretion of the pituitary hormone ACTH has been observed in a number of ovarian tumors and cell lines and has been implicated in the development of Cushing's syndrome among ovarian cancer patients in rare cases [26, 27]. The apoptotic mediators DR5, Fas, and FasL have each been previously investigated in ovarian cancer resulting in the observations that elevated DR5 expression correlates with decreased overall survival [28], and the macrophage infiltrate in ovarian cancer expresses high levels of Fas and FasL [29]. Although specific roles for IGFBP-1, TNFRI, and Kallikrein 10 remain to be characterized, these biomarkers have all been shown previously to be associated with the development and progression of ovarian cancer [30-32].…”
Section: Discussionmentioning
confidence: 99%